Experience and Application Possibilities of Scanning Devices for Monitoring Radiation Fields in Shut-Down Uranium–Graphite Reactors - Pavlyuk (Pavliuk) A. O. Aleksander Olegovich; Kotlyarevsky S. G. Sergey Gennadjevich; Kan Roman Igorevich R. I.; Zelenetskaya E. P. Ekaterina Petrovna (2024, 2024)
Title screen